Prevalence evaluation of ocular injuries of different kinds as zygomatic fractures consequences in patients referring to department of oral and maxillofacial surgery, Shariati Hospital (Oct 2004-Oct 2 - Mahmood Hashemi H. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: Zygomatic fractures are common among oral and maxillofacial problems and ocular injuries are of great importance, the prevalence of ocular problems following zygomatic fractures in Iran is not clear so we performed this study to evaluate this problem in patients referring to Shariati Hospital. "nMaterials and Methods: In this descriptive, cross-sectional study, we evaluated the patients who referred to department of oral and maxillofacial surgery of Shariati hospital for ocular complains following zygomatic fractures. The evaluation was performed both clinically and historically. "nResults: 115 patients were examined (87 males and 28 females) with the mean age of 26 for males and 32 for females. The prevalence of ocular injuries were as follows: subconjunctival ecchymosis: 23.07% for males and 21.05% for females. Displacement of palpebral fissure: 26.5% for males and 27.6% for females. Unequal papillary levels: 18.37% for males and 15.78% for females. Diplopia: 8.9% for males and 10.5% for females. Enophthalmos: 23.1% for males and 25% for females. "nConclusion: It is strongly recommended to refer patients with zygomatic fracture for an ophthalmologic consultation.